MODELAGEM DE EQUAÇÕES ESTRUTURAIS APLICADA ÀS RELAÇÕES ENTRE AUTONOMIA INDIVIDUAL, INNOVATIVENESS E PERFORMANCE NO INSS - Conceição, Felipe Ricardo da Costa (2021)
Over the last decade, Brazilian public organizations have been pressured to respond swiftly and transparently to new social demands, a fact made worse by the Covid-19 pandemic, which has made the public sector`s response to society even more complex and urgent. Given this situation, public organizations directed their efforts towards innovation. In the context of the National Institute of Social Security (INSS), it was no different, as in seeking greater efficiency in the analysis of social security demands, this institute implemented innovations that expanded the autonomy of its employees through reformulation of its service processes, creation of semi-presential management programs and adoption of telework. The problem at hand is that these measures were taken without knowing a priori their impacts on innovativeness (capacity to innovate) or on organizational performance. Thus, the main objective of the research carried out was to understand how individual autonomy impacts organizational performance in the INSS. Although it is already known that an organization with a greater capacity to innovate is more likely to perform better when compared to less innovative organizations, the role of individual autonomy in this relationship is not clear, which is why a theoretical framework that includes field studies was adopted. of organizational innovation. As for the methods and procedures, the research was characterized as quantitative, with the application of a questionnaire to managers throughout the INSS, in order to measure autonomy, innovativeness and organizational performance. The data obtained were analyzed using the structural equation analysis technique (CB-SEM), whose results support the hypotheses raised: in the INSS, innovativeness positively impacts organizational performance; moreover, individual autonomy is a factor in the ability to innovate, which is the most relevant theoretical contribution of this study. Based on the results, as a Technical/Technological Product, a Conclusive Technical Report was prepared, proposing measures for the INSS to increase its capacity to innovate and, indirectly, further improve its organizational performance.